A Raman spectroscopy bio‐sensor for tissue discrimination in surgical robotics. Issue 1 (21st June 2013) - Ashok, Praveen C.; Giardini, Mario E.; Dholakia, Kishan; Sibbett, Wilson
Abstract We report the development of a fiber‐based Raman sensor to be used in tumour margin identification during endoluminal robotic surgery. Although this is a generic platform, the sensor we describe was adapted for the ARAKNES (Array of Robots Augmenting the KiNematics of Endoluminal Surgery) robotic platform. On such a platform, the Raman sensor is intended to identify ambiguous tissue margins during robot‐assisted surgeries. To maintain sterility of the probe during surgical intervention, a disposable sleeve was specially designed. A straightforward user‐compatible interface was implemented where a supervised multivariate classification algorithm was used to classify different tissue types based on specific Raman fingerprints so that it could be used without prior knowledge of spectroscopic data analysis. The protocol avoids inter‐patient variability in data and the sensor system is not restricted for use in the classification of a particular tissue type. Representative tissue classification assessments were performed using this system on excised tissue. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)